Knowledge, attitude and experiences of menopause in the postmenopausal women at a tertiary care center: a cross sectional study - More, Shivraj; P., Sujatha; Karthiga, Karthiga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Menopause is an inevitable milestone in the reproductive life of every woman. The objective is to investigate menopausal knowledge, attitude, symptoms and management among the participants, to identify the differences according to their educational status and to examine correlations of knowledge, attitude and symptoms pertaining to menopause. Methods: This cross-sectional study was conducted for a period of 10 months in postmenopausal women attending a tertiary care center in Pondicherry, India with a structured questionnaire developed on the basis of the objective of the study. Results: 330 postmenopausal women were recruited, and all were aware of their postmenopausal status. Mean age at menopause was 45.91±2.66 years. 54.5% were aware about what menopause was while 5.5% were unaware. 12.1% had proper knowledge about cause of menopause, whereas 3.6% said it is due to god’s decision / turning point. Most prevalent symptoms were tiredness (89.6%) followed by vasomotor symptoms like hot flushes (88.5%) and night sweats (80.3%). Only 2.1% had used HRT for menopausal symptoms. Conclusions: Depth of knowledge is more important when concern is about greater health disrupter which tends to be imperceptible for a long time such as bone health and cardiovascular risk profile. Thus, the government could concentrate on providing health services to women in post reproductive age group also besides women in the reproductive age.